The triumphant tale of the house sparrow - Thornhill, Jan (Groundwood Books, House of Anansi Press, 2018)
Presents the history of the house sparrow, from its beginnings in the Middle East to its spread with the growth of agriculture around the world, and discusses its population decline in recent years.